Can Previous Chemotherapy Affect the Outcome of Nivolumab Treatment in Non-small Cell Lung Cancer - Svaton, Martin; Bratova, Monika; Koubkova, Leona; Fischer, Ondrej; Melichar, Bohuslav; Hrnciarik, Michal; Dolezal, Daniel; Bilek, Ondrej; Krejci, Jana; Drosslerova, Marie; Dlouha, Zdenka; Blazek, Jiri; et al. (Anticancer research, 2022)
AIM: This study compared the results of nivolumab treatment in patients with pulmonary adenocarcinomas based upon previous chemotherapeutic regimens. PATIENTS AND METHODS: The data source for this retrospective study was the Czech VILP registry of patients with nivolumab-treated adenocarcinomas in second and higher lines of treatment. In relation to objective response rate, progression-free interval, and overall survival, three comparisons of patient were made: A: Those treated in first line with cisplatin and pemetrexed versus carboplatin with paclitaxel or vinorelbine; B: treatment with cisplatin and pemetrexed versus carboplatin with paclitaxel/vinorelbine and bevacizumab; and C: treatment in previous lines with pemetrexed (first-line cisplatin and pemetrexed plus those treated in second line with pemetrexed) versus treatment with taxane (first-line carboplatin and paclitaxel only plus those treated with second-line docetaxel). RESULTS: We observed no differences in objective response rate or progression-free survival between patients treated with the stated chemotherapeutic regimens. We observed a trend towards better overall survival for patients treated with carboplatin plus taxanes or vinorelbine with/without bevacizumab. CONCLUSION: From our overall survival data, a chemotherapeutic regimen of carboplatin plus taxanes or vinorelbine with/without bevacizumab might be a better partner for immunotherapy than a cisplatin and pemetrexed-based one.
Keywords: nádory plic; protokoly protinádorové kombinované chemoterapie; Lung Neoplasms; lidé; retrospektivní studie; nivolumab; Retrospective Studies; Carcinoma, Non-Small-Cell Lung; nemalobuněčný karcinom plic; Nivolumab; Antineoplastic Combined Chemotherapy Protocols; Humans